The Impact of Occupational Health and Safety on Organizational Commitment at Sugar Companies Factories in Sudan - Abdelkhair, Farah Yasin Farah; Mohammed, Hamid Altaib; Babekir, Mamoun Yaseen Badawi; Alawad, Sara Suliman (Journal of Economic, Administrative and Legal Sciences, 2021)
The study presented a problem related to knowing the impact of occupational safety and health on organizational commitment in sugar companies’ factories in Sudan, as it aimed to verify the impact of occupational safety and health on organizational commitment. The study followed the descriptive and analytical approach, in which a questionnaire was designed and distributed to a random sample of (256) employees in (3) factories of sugar companies in Sudan (Sinnar, White Nile, and Kenana). The most important findings of the study were: that the practices of occupational safety and health and organizational commitment were characterized by an increase with arithmetic averages of 3,883 and 4,041, respectively; the results of the study also showed a statistically significant impact of occupational safety and health on organizational commitment (continuity commitment, emotional commitment, and normative commitment). Finally, the study presented a set of recommendations to support decision-makers in the sugar industry and in sugar companies' factories in Sudan to build and enhance occupational safety and health as a catalyst for organizational commitment of employees.
Keywords: Safety; Occupational Health; Regulatory Compliance; Sugar Factories